Producing root cultures of the Hedysarum enaffae (Experimental biology, 2015)
Root cultures produced using wild non-modified Agrobacterium strains are of high practical interest in terms of their biological safety for development fitodrugs on the base of medicinal plants. Root cultures of Hedysarum enaffae were produced by inoculation with Agrobacterium rhizogenes 15834Sw strain and their morphological characteristics were studied. Isolated roots were characterized with dark coloring and both root types had capacity to stem organogenesis. Hairy roots had light coloring and were a mixture of clear appeared roots with small quantity of proliferating suspension cells which are separated from friable surface of growing roots and grow in suspension form. Both root types had high growing rate and root indexes after cultivation during 8 weeks were 30 at isolated and 50 at hairy roots accordingly.
Keywords: endemic; Hedysarum; medicinal plants; isolated roots; “hairy roots”; root culture in vitro; Agrobacterium rhizogenes; biologically active substances.